Influence of subclinical hypothyroidism on parameters of tear production in patients with hypertension - Ye. V. Novikov (Zaporožskij Medicinskij Žurnal)
A high incidence, continuous growth rates as well as collected data on modifying influence of subclinical hypothyroidism (SH) on cardiovascular disease, necessitate the improvement of clinical diagnostic methods of hypothyroidism at the early stages. Thyroid hypofunction has been proved to be influential in the tear fluid secretion and dry eye syndrome development. However, there is insufficient evidence of tear production parameters use for hypothyroidism diagnosis at the preclinical stages in patients with cardiovascular disease.